The Consequences of Social Responsibility: A Study of Fast Fashion Brands - Ekasari, Ayu; Fajaray, Ariani (Business and Entrepreneurial Review, 2023)
This research aims to analyze the positive impact of social responsibility carried out by fast fashion brand on consumers’ attitude, trust, perceived consumer effectiveness and brand awareness. Using purposive sampling method, there were 175 respondents participated in the survey. The data was analyzed using structural equation model. The results revealed that brand’s social responsibility activities influence attitude, trust, perceived consumer effectiveness and brand awareness. However, the authors did not find any significant effect of perceived consumer effectiveness and brand awareness on purchase intention. This research can help fast fashion marketers to design a comprehensive message to convey to public that they carry out CSR programs. This study contributes to the literature of green marketing by examining the effect of CSR conducted by fast fashion brand on various response of consumers. The findings can help companies to design and communicate appropriate CSR initiatives in order to enhance consumers’ positive perception. Keywords: Corporate social responsibility, attitude, trust, perceived consumer effectiveness, brand awareness, purchase intention.